2007
DOI: 10.1021/ie070393b
|View full text |Cite
|
Sign up to set email alerts
|

Selected Chloro-Organic Detoxifications by Polychelate (Poly(acrylic acid)) and Citrate-Based Fenton Reaction at Neutral pH Environment

Abstract: The use of chelating agents to modify the Fenton reaction is well-documented in the literature. Polymeric chelates (such as poly(acrylic acid), PAA) provide multiple binding sites and can complex iron ion (ferrous/ ferric ion) and prevent ferric hydroxideprecipitation even at neutral pH environment. In this study, it was proven that poly(acrylic acid) could act as a polychelate in the modified Fenton reaction for the oxidation of chlorinated organic compounds (such as 2,2′-dichlorobiphenyl and biphenyl) at neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In addition to the speciation of iron, the [L]:[Fe] ratio plays an important role in determining the rate of H 2 O 2 degradation. This rate decreases as this molar ratio is increase from 1:1 to 4:1 and, in conjunction with other findings, indicates Fe–citrate complexes are nonreactive with H 2 O 2 when compared to uncomplexed iron (Li et al , 2007b). Increasing the L:Fe ratio increases the efficiency of H 2 O 2 consumption by reducing the rate of hydroxyl radical production.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to the speciation of iron, the [L]:[Fe] ratio plays an important role in determining the rate of H 2 O 2 degradation. This rate decreases as this molar ratio is increase from 1:1 to 4:1 and, in conjunction with other findings, indicates Fe–citrate complexes are nonreactive with H 2 O 2 when compared to uncomplexed iron (Li et al , 2007b). Increasing the L:Fe ratio increases the efficiency of H 2 O 2 consumption by reducing the rate of hydroxyl radical production.…”
Section: Resultssupporting
confidence: 83%
“…The use of a chelate for remediation in aerobic environments minimizes Fe(II) oxidation by O 2 . Li et al (2007b) demonstrated that dissolved oxygen has no effect on the degradation of trichlorophenol (TCP) by the chelate-modified Fenton reaction using polyacrylic acid (PAA) as the chelating agent. Sun and Pignatello (1992) documented the interactions of dozens of chelating agents, such as EDTA and catechol, with Fe(III) as well as their effect on the reactivity of the Fe(III)–chelate complexes with H 2 O 2 for 2,4-D oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a chelate for remediation in aerobic environments minimizes Fe 2+ oxidation by O 2 . Dissolved oxygen has no effect on the degradation of trichlorophenol by the chelate-modified Fenton's reaction using polyacrylic acid as the chelating agent [14]. Most of the tested chelates for Fenton's reaction in the literature are of …”
Section: Discussionmentioning
confidence: 99%
“…However, industrial wastewater often contains chelating agents such as detergents, stabilizers, and masking agents for metallic ions, which have a potential to inhibit the iron-based advanced oxidation process through masking of iron. Li et al (2007b) demonstrated that chelating agents of citrate and poly(acrylic acid) constrained the Fenton reaction by lowering free Fe…”
Section: Introductionmentioning
confidence: 99%